Optimized Case Finding of tuberculosis among key populations in Ukraine. A follow up study - Liliia, Masiuk; Geliukh, Evgenia; Islam, Zahedul; Davtyan, Hayk (The Journal of Infection in Developing Countries, 2024)
Introduction: In 2021, there were 4 million tuberculosis (TB) cases that were not detected by health systems, globally. Many of those cases are among hard-to-reach populations or key population groups. An Optimized Case Finding (OCF) strategy was introduced in Ukraine to enhance case detection and identify those “missing” cases. OCF included screening of up to eight referred household and social network contacts of an index TB case. Following the OCF project implementation, TB detection and characteristics of index cases and contacts were assessed. Methodology: A cohort study using project data (July 2018 – April 2022) was conducted. Results: In total 7,976 close contacts were engaged in the project from 1,028 index TB cases. Among the contacts, 507 were diagnosed with TB. The TB case detection was 6,356/100,000 and the number needed to investigate was 16. Multiple factors were identified as associated with TB detection including smoking, HIV, poverty, etc. About 90% of cases were identified at the initial screening of the contacts. OCF was proven to be 5.8 times more effective than the standard active case finding using household surveys and 106 times more effective than passive case finding in the general public. Conclusions: Our study demonstrated the effectiveness of OCF in detecting cases among key population groups and their social networks. We encourage adaptation and use of OCF by civil society organizations that already work with key vulnerable populations around the globe.